LEGAL ANALYSIS OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF ADMINISTRATIVE ACTIONS IN IMMIGRATION (A RESEARCH STUDY AT THE CLASS II IMMIGRATION OFFICE OF TANJUNG BALAI KARIMUN) - Ramono Winawan; Soerya Respationo; Parameshwara (CV. RADJA PUBLIKA, 2025)
Border areas such as Tanjung Balai Karimun have a strategic position as entry and exit points for foreign nationals (WNA), thus requiring strict and effective immigration supervision. One form of such supervision is the implementation of immigration administrative measures, as stipulated in Law No. 6 of 2011 concerning Immigration. However, in practice, the implementation of administrative measures such as refusal of entry, deportation, and prevention still faces various obstacles. This study aims to analyze the legislation, implementation, obstacles, and solutions for the implementation of immigration administrative measures at the Tanjung Balai Karimun Class II Immigration Office. This study uses a normative legal approach and an empirical legal approach with a sociological approach (socio-legal approach). Legal materials were obtained through document studies, interviews with immigration officials, and direct observation of the implementation of administrative measures in the field. The results of the study indicate that, from a normative perspective, the laws and regulations governing administrative measures are adequate and comprehensive, supported by implementing regulations such as Government Regulation No. 31 of 2013 as amended by Government Regulation No. 40 of 2023 and Ministerial Regulation No. 2 of 2025. However, from an implementation perspective, its implementation remains ineffective due to limited human resources, inadequate intelligence training, a lack of supporting facilities, weak inter-agency coordination, and low public legal awareness. Therefore, increasing institutional capacity, enhancing cross-sectoral coordination, utilizing intelligence technology, and providing legal education to the public are necessary strategies to systematically improve the effectiveness of immigration administrative actions.